Analisis Maqashid Syariah terhadap Praktik Sebambangan dalam Perkawinan Adat Lampung - Bela Asri Pratiwi; Jayusman (Journal of Legal Sustainability, 2026)
This tradition has become part of the cultural identity of the Pepadun and Saibatin Lampung communities, but its existence contains significant normative complexities when confronted with Islamic legal standards that uphold the dignity of every individual (Iman et al., 2024; Romadhon et al., 2024). (2) Objectives: This study aims to analyze the suitability of the sebambangan practice with the principles of maqashid sharia, specifically hifẓ al-nafs, hifẓ al-’aql, hifẓ al-nasl, hifẓ al-’irdh, and hifẓ al-mal, and to formulate a reconstruction model that combines the preservation of customs with Islamic values. (3) Method: This study uses a qualitative approach with socio-legal methods through literature review, supported by interviews with traditional leaders, religious leaders, and sebambangan practitioners, as well as analysis of customary documents and applicable marriage regulations. (4) Results: The findings indicate that although sebambangan has been acculturated with Islamic values ​​and recognized as a living ’urf in Lampung society, its contemporary practice still contains the potential to weaken the protection of women’s lives, minds, and honor, primarily due to the absence of an explicit mechanism for verifying consent and the presence of social pressures that have the potential to hinder women’s free will. (5) Conclusion: Sebambangan can only be maintained and categorized as ’urf ṣaḥīḥ if procedural reconstruction is carried out that guarantees the consent of both brides, protection of women’s dignity, and compliance with the requirements of marriage in Islamic law.